Assessment of the novel platinum(IV) complexes effects on female rats' kidneys: Possible nephroprotection of resveratrol - Paunović, Milica G.; Matić, Miloš M.; Obradović, Ana D.; Stanković, Vesna D.; Jevtić, Verica V.; Ognjanović, Branka I. (Journal of inorganic biochemistry, 2026)
Due to cisplatin's limited efficacy and adverse effects on healthy tissues, particularly the kidneys, its use is restricted. The objective of this research was to investigate the impact of new Pt(IV) complexes that contain ethyl- propyl- and butyl-esters of the ethylenediamine-N,N′-di-S,S-(2,2′-dibenzyl) acetic acid, as well as possible advantages of resveratrol co-treatment, on the kidneys of female Wistar albino rats by detecting kidney injury markers, oxidative stress parameters and morphological tissue changes. The rats, divided into ten groups, received a single intraperitoneal dosage of cisplatin (7.5 mg/kg) or Pt(IV) complexes (10 mg/kg), and/or resveratrol (25 mg/kg), whereas the control animals received only an ip injection of saline. Acute complexes treatments increased Chl value while decreasing Gl, Cre, and Urea levels, suggesting kidney injury. Novel compounds considerably decreased the levels of O2•−, H2O2 and GSSG, while raising the levels of NO2−, LPO and GSH. In addition, the activities of SOD, GSH-Px, and GST were increased, while the activities of CAT and GR were alleviated. Regarding morphological changes in kidney tissue, they were mostly of mild intensity. Results indicate that used complexes might trigger an imbalance of redox equilibrium of kidney cells and that the renal tissue was more vulnerable to the negative effects of Pt(IV) complexes than to cisplatin. Resveratrol's nephroprotective benefits were not shown. Additionally, a prooxidative effect was registered after co-treatments. These findings could be useful for future studies in clarifying how the investigated compounds act in the estradiol-rich environment and how they affect the tissues of male rats. In vivo effects of novel platinum(IV) complexes alone and in co-treatment with resveratrol on redox homeostasis of kidney tissue cells of female rats. Novel complexes exhibit redox potential and provoke oxidative stress and lipid peroxidation. Resveratrol in the examined co-treatment didn't show protective activity. [Display omitted] •Pt(IV) complexes caused the redox imbalance of rat kidney tissue cells.•Pt(IV) complexes induced oxidative stress and lipid peroxidation.•Pt(IV) complexes provoked the alteration of the antioxidative defence system.•Pt(IV) complexes exerted similar nephrotoxicity compared to cisplatin.•Resveratrol does not have any protective benefits against induced nephrotoxicity.